The Welfare and Distributional Effects of Increasing Taxes on Tobacco in Vietnam - Fuchs Tarlovsky, Alan; Gonzalez Icaza, Fernanda (World Bank, Washington, DC, 2019)
This paper assesses the welfare and distributional effects of raising taxes on tobaccoin Vietnam. Tobacco taxes are recognized as effective policy tools to reduce tobaccoconsumption and to improve health outcomes. However, policy makers often hesitateto use them because of claims of their potentially regressive effects. According to thoseclaims, poorer households are particularly hurt by tobacco tax policies, as cigarettepurchases represent a larger share of their budgets relative to higher-income smokers.The paper argues that the claims on the regressive effects of tobacco tax policies arebased on naive, shortsighted, and incorrect estimations. Tobacco-related illnessesdamage health outcomes and the quality of the lives of smokers and their families, whilethey also cost billions of dollars in medical expenditures and losses in human capital andproductivity every year. Tobacco consumption imposes heavy economic burdens onhouseholds and governments, in addition to its well-known negative health and socialimpacts. Raising taxes on cigarettes dissuades consumption, hence improving healthoutcomes, adverting premature deaths, and reducing direct and indirect economic costs.The analysis applies the Extended Cost Benefit Analysis (ECBA) methodology to simulateempirically the costs, as well as the benefits of increasing the prices on cigarettes onthe welfare of Vietnamese households. Following a well-established body of literature,the ECBA acknowledges that there may be short-term direct negative effects of raisingprices on tobacco, as smokers can struggle to continue to purchase tobacco with theirunchanged household budgets. However, the model also incorporates two of the mainbenefits of reducing tobacco consumption by increasing taxes: (a) the reduction insmoking-related medical expenses borne by households and (b) the additional incomesthat households can earn by preventing years of productive life lost due to smoking attributablepremature deaths. A critical contribution of the ECBA is to incorporate decile-specific price elasticities of demand for cigarettes, to quantify the behavioral responses or sensitivity of smokers in different income groups to changes in cigarette prices. To the knowledge of the authors, this is the first available empirical exercise to estimate price elasticities by income decile in Vietnam. Consistent with the literature and with empirical findings in other countries, the price elasticities of demand for cigarettes are larger for lower-income households. Lower income smokers are likely to reduce their tobacco consumption more drastically, when faced with a price increase. The ultimate distributional effect on welfare of the increasein the price of cigarettes due to tax increases will then depend on assessing the potentialbenefits against the short-term costs.